2023
DOI: 10.1515/reveh-2022-0216
|View full text |Cite
|
Sign up to set email alerts
|

Hospital wastewater treatment methods and its impact on human health and environments

Abstract: The scientific development and economic advances have led to the identification of many pathogenic agents in hospital effluents. Hospital wastewaters are qualitatively similar to municipal wastewaters, with the difference that these wastewaters contain toxic and infectious substances and compounds that can be dangerous for the health of the environment, employees of these centers, and the entire community. Therefore, in the last few years, it has been emphasized that all hospitals and medical and health center… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…4.3.5 Contamination of potable water from healthcare industry waste. Environmental quality and public health can be negatively impacted by water contamination (Ram ırez-Coronel et al, 2023). Wastewater from healthcare industries is qualitatively comparable to municipal wastewater, except that they contain infectious and toxic compounds that can harm public health and the environment (Ram ırez-Coronel et al, 2023).…”
Section: Healthcare Industry Wastementioning
confidence: 99%
See 2 more Smart Citations
“…4.3.5 Contamination of potable water from healthcare industry waste. Environmental quality and public health can be negatively impacted by water contamination (Ram ırez-Coronel et al, 2023). Wastewater from healthcare industries is qualitatively comparable to municipal wastewater, except that they contain infectious and toxic compounds that can harm public health and the environment (Ram ırez-Coronel et al, 2023).…”
Section: Healthcare Industry Wastementioning
confidence: 99%
“…Environmental quality and public health can be negatively impacted by water contamination (Ram ırez-Coronel et al, 2023). Wastewater from healthcare industries is qualitatively comparable to municipal wastewater, except that they contain infectious and toxic compounds that can harm public health and the environment (Ram ırez-Coronel et al, 2023). Health risk for public health has been reported by numerous studies due to high levels of metals, nitrates, organic pollutants and fluoride in water (Zhang & Zhou, 2020).…”
Section: Healthcare Industry Wastementioning
confidence: 99%
See 1 more Smart Citation
“…The presence of fecal bacteria, including pathogens, in various ecosystems could be a sign of major pollution and a warning signal for public health, especially when bacteria develop adaptation and resistance mechanisms to pharmaceutical compounds, which are massively used in hospitals [3]. Recently, Ramirez-Coronel and collaborators showed that wastewaters from hospitals and medical centers could play a significant role in spreading pathogenic bacteria and subsequently infectious diseases over large areas of the aquatic environment [4]. In addition, hospital wastewaters contain larger loads of infectious microorganisms compared to urban wastewaters, and unfortunately, they can pass and dissipate the bacterial resistance to some pharmaceutical compounds, by lateral gene transfer, to other microorganisms in urban wastewaters and environments [5].…”
Section: Introductionmentioning
confidence: 99%